Market Response to Deregulation of Swedish Pharmacies: An Empirical Study on Consumers' Opinion in Stockholm City - Baishya, Arup K. (Indian Journal of Marketing, 2012)
The Swedish Government deregulated the pharmacy market in 2009, ending a four-decade long monopoly of the state-run Apoteket AB and opening the market for other competitors. This transition from monopoly to free market generated high level of expectations from consumers. In an attempt to shed light on the complex changes concomitant with the deregulation and to analyze the liberalized market, this paper studies the public opinion on deregulation and consumers' expectations from the pharmacy market. The study found Swedish consumers to be overwhelmingly supportive of the deregulation, and they expected higher accessibility, better quality drugs and improved service level. Based on the results, suggestions have been made for increasing opening hours, process improvement using Six Sigma and designing a people focused marketing mix. Proposition for a new framework of customer service management (CSM), called "ICTAS Framework" is put forward for consideration.